ANALISIS STATISTIK REGRESI RETURN ON ASSETS PERUSAHAAN INVESTASI DI INDONESIA - Tripermata, Lukita (Universitas Indo Global Mandiri Palembang, 2022)
This study aims to analyze the debt to asset ratio, public share ownership and company size to the return on assets of investment companies in Indonesia. The data sample used in this study is a comprehensive profit report on (8) eight investment companies listed on the Indonesia Stock Exchange. Data analysis using regression statistics. The results of the study explained that the debt to asset ratio and public share ownership have proven to have a positive and significant effect on return on assets. The size of the company does not have a significant effect on the return on assets.